3D numerical modelling of graben interaction and linkage: a case study of the Canyonlands grabens, Utah. (20th March 2013) - Allken, Vaneeda; Huismans, Ritske S.; Fossen, Haakon; Thieulot, Cedric
Abstract Graben systems in extensional settings tend to be segmented with evidence of segment interaction. To gain a better understanding of the evolution of structures formed during graben growth and interaction, we here study the Grabens area of Canyonlands National Park, Utah, where a wide range of such structures is well exposed. With the aid of 3D numerical models, we attempt to reproduce structures observed in that region and to understand controls on the structural style of graben interaction by varying the spacing between pre‐existing structures. The sensitivity of the system to the thickness of the salt layer is also tested. Four distinct types of structures are observed when the spacing between inherited weak zones is varied: (1) grabens connecting in a relay zone divided by a narrow central horst; (2) graben segments interacting via a secondary stepover graben; (3) grabens propagating alongside each other with limited segment interaction; and (4) an abandoned graben segment in a system of multiple competing grabens. The presence of a basal salt layer (Paradox Member) promotes efficient graben propagation. A comparison between the observed structures and the numerical model results indicates that the detachment salt layer is relatively thin in the study area.